2014
DOI: 10.1080/07391102.2014.907543
|View full text |Cite
|
Sign up to set email alerts
|

How does the protein environment optimize the thermodynamics of thiol sulfenylation? Insights from model systems to QM/MM calculations on human 2-Cys peroxiredoxin

Abstract: Protein thiol/sulfenic acid oxidation potentials provide a tool to select specific oxidation agents, but are experimentally difficult to obtain. Here, insights into the thiol sulfenylation thermodynamics is obtained from model calculations on small systems and from a quantum

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 40 publications
(41 reference statements)
1
12
0
Order By: Relevance
“…It has been proposed that Ser26 does not govern ligand selectivity through sidechain H bond interactions, since a fully transport-active AdiC S26A mutant shows a normal capacity to distinguish Arg + from Arg +2 11 , 30 . However experimental and theoretical studies, however, have shown that water molecules can, in some cases, take over the role of the mutated residue within the binding pocket 31 , 32 . One can therefore not totally rule out the possibility that the Ser26 sidechain or a replacing bound water molecule might act in a local mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It has been proposed that Ser26 does not govern ligand selectivity through sidechain H bond interactions, since a fully transport-active AdiC S26A mutant shows a normal capacity to distinguish Arg + from Arg +2 11 , 30 . However experimental and theoretical studies, however, have shown that water molecules can, in some cases, take over the role of the mutated residue within the binding pocket 31 , 32 . One can therefore not totally rule out the possibility that the Ser26 sidechain or a replacing bound water molecule might act in a local mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the size of the protein (10079 atoms) structural optimization is performed using the CHARMM27 force field 28 for protein and water molecules, while the capping N-terminal N-carbamoyl-alanine (NCB) residue is described by a custom CHARMM topology file, for which atom typing and assignment of parameters and charges are taken from an analogous residue. Details of the topology file and of the parameters of NCB can be found in the supporting information of a previous publication by some of the present authors 29 . All modeling calculations are carried out using the CHARMM software package 30 .…”
Section: Methodsmentioning
confidence: 99%
“…All modeling calculations are carried out using the CHARMM software package 30 . The S -form of cysteine is created using a previously published patch residue 29 . Parameters for the S -form were previously published 31,32 .…”
Section: Methodsmentioning
confidence: 99%
“…All of the above mechanisms favor thiolate form over thiol; therefore, their efficiency is highly sensitive to cysteine pKa (the more nuanced discussion of the pKa dependence can be found elsewhere 41 , 42 ). More generally, in the context of structured proteins the efficiency of these reactions can be greatly influenced by electrostatic and steric factors and vary by many orders of magnitude 43 .…”
Section: Resultsmentioning
confidence: 99%